The Role of Psychological and Social Factors in the Acquisition of Arabic as a Second Language - Siska Qurrota A'yun; Talitha Rahma Azzahra (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2026)
The acquisition of Arabic as a second language is influenced by the dynamic interaction of psychological and social factors. This study examines how internal psychological dimensions—such as motivation, self-confidence, and anxiety—interact with social environments in shaping learners’ ability and willingness to actively use Arabic. Using a qualitative library-based research approach, this study analyzes 25 scholarly sources published between 2020 and 2025 through thematic content analysis. The findings reveal that psychological factors, particularly anxiety and self-confidence, play a dominant role in determining learners’ communicative engagement, while social environments function as critical reinforcement that either strengthens or weakens these psychological conditions. Supportive social contexts, including interaction with native speakers and access to technology-based learning resources, significantly reduce anxiety and enhance learners’ confidence. This study highlights that Arabic language acquisition becomes more effective when psychological readiness and social support operate in synergy. The findings contribute to Arabic language education by emphasizing the importance of integrating psychological support and social learning environments to improve instructional practices for non-native Arabic learners.